The modulation of memory by item-typicality and schema congruency in Alzheimer's Disease and Autism Spectrum Disorder: Examining the role of the hippocampus. - Souza, C.; Garrido, M. V.; Joana C. Carmo (XIII PhD Meeting in Social and Organizational Psychology, 2017)
Memory is central to many cognitive processes, impacting in future decisions for a better social adaptation. For example, every day when we wake up, we plan our day based on long-term memories, as our previous experiences (episodic memory) and also as our general knowledge (semantic memory).Long-term memory theories suggest that the hippocampus sustains memories formation, but disagree upon the participation of this structure in all types of declarative memories. Also, the idea that hippocampal structures support the development of an abstract (semanticized) version of episodic memory traits in cortical areas remains in debate.In healthy-individuals, the conceptual knowledge (i.e., schemas and item-typicality) enhances memory formation (episodic traits). However, in Autism-Spectrum-Disorder (ASD) and Alzheimer’s Disease (AD) there is no benefit from conceptual knowledge, specially item-typicality, when forming episodic memories. A possible explanation is that both clinical groups have hippocampus damage or alterations.This project examines the role of encoding schema (abstract mental representation) and item-typicality (goodness of an exemplar to represent its category) on episodic and semantic memories systems. We will contrast typical developmental (TD) adults with ASD-group as well as comparing AD-group with TD-elderly group in a recognition memory task with the remember-know paradigm. The innovativeness of this proposal rests on indirectly comparing the neurocognitive profile of two clinical groups with robust behavioral and fMRI measures. The project is likely to clarify the semantic-episodic system relationship, particularly the role of the hippocampus-cortical network, and to uncover neurocognitive signatures in these clinical populations for earlier diagnosis and rehabilitation purposes.